2019
DOI: 10.1038/s41467-019-09255-1
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-region sequencing unveils novel actionable targets and spatial heterogeneity in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) ranks fourth among cancer-related deaths in China due to the lack of actionable molecules. We performed whole-exome and T-cell receptor (TCR) repertoire sequencing on multi-regional tumors, normal tissues and blood samples from 39 ESCC patients. The data revealed 12.8% of ERBB4 mutations at patient level and functional study supported its oncogenic role. 18% of patients with early BRCA1 /2 variants were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
137
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(152 citation statements)
references
References 61 publications
14
137
0
1
Order By: Relevance
“…Targeted drugs directed against molecules involved in the pathogenesis and progression of cancer have achieved successful clinical outcomes in other cancers. Genomic profiling using next-generation sequencing (NGS) has been conducted and has identified some candidate therapeutic targets for ESCC (19)(20)(21). However, clinical studies have shown that effective singletarget drugs for ESCC are still lacking because of the complexity of signaling networks.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted drugs directed against molecules involved in the pathogenesis and progression of cancer have achieved successful clinical outcomes in other cancers. Genomic profiling using next-generation sequencing (NGS) has been conducted and has identified some candidate therapeutic targets for ESCC (19)(20)(21). However, clinical studies have shown that effective singletarget drugs for ESCC are still lacking because of the complexity of signaling networks.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the presence of subclones of tumor cells harboring different genomic alterations has become abundant with the advent of new technologies such as multiregional and single-cell sequencing. 12,13 A seminal study by Gerlinger et al in 2012 identified that approximately two-thirds of somatic mutations are not detectable across every region within a tumor. 14 Single-cell sequencing of malignant HNSCC cells reveals high variability in expression signatures related to cell cycle, stress, hypoxia, and epithelial to mesenchymal transition.…”
Section: Tumor Heterogeneitymentioning
confidence: 99%
“…Spatial intratumor heterogeneity has been elucidated at high resolution in many cancer types [15,36,37,38,39,40]. Recently, several groups have performed multi-regional deep-sequencing, and have presented a comprehensive heterogeneous landscape of ESCC [41,42,43,44]. Through analyzing 51 sub-tumor regions from 13 ESCC patients, Hao et al [42] proposed that approximately 40% of driver mutations were spatially heterogeneous, including oncogenes such as KIT , and members of the PI3K / MTOR ( PIK3CA and MTOR ) and NFE2L2 pathways ( NFE2L2 and KEAP1 ).…”
Section: Intratumor Heterogeneitymentioning
confidence: 99%
“…These seemingly surprising data indicate that diversified mutational backgrounds were already established in the precursor lesion or even normal esophageal epithelia, conferring on the esophageal cells the ability to evade selection pressure during ESCC development. Moreover, the degree and complexity of spatial heterogeneity was found to be highly correlated with ESCC aggressiveness [44]. Specifically, clinical stage of ESCC was negatively correlated with the proportion of ubiquitous mutations, and significantly more heterogeneous mutations were observed in ESCC patients with local metastasis, compared to those without.…”
Section: Intratumor Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation